POSSIBILITIES OF USING THE EXPERIENCE OF FOREIGN COUNTRIES IN THE DEVELOPMENT OF FISHERIES IN COUNTRIES WITH DIFFERENT FORMS OF OWNERSHIP - Beglayev, Uchqun Khurramovich (THE INNOVATION ECONOMY, 2026)
This article examines the experience of foreign countries—China, Vietnam, and Kazakhstan—as well as the key criteria for farmed fish products and their management mechanisms. It also highlights the long-term, medium-term, and annual development strategies of these countries.